Community’s acceptance of biscuits with substitution of gude bean flour (cajanus cajan (l.) millsp) and mocaf flour - Nurul Inayah; Aswita Amir; Hendrayati Hendrayati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
Protein Energy Deficiency (PEM) is one of the nutritional problems in Indonesia. The use of gude peanut flour and MOCAF flour in making biscuits to increase protein content and can reduce or prevent one of the nutritional problems, namely PEM. Knowing the community's acceptance of biscuits by substitution of gude peanut flour (Cajanus cajan (L.) Millsp) and MOCAF flour. This research is a quasi-experimental research design using a post test design group. The community's acceptance of the biscuits with substitution of MOCAF and Gude peanut flour was assessed based on 4 hedonic test scales, is very like, like, dislike and very dislike of 25 rather trained panelists. The results of the research on the manufacture of flour weighing 1,925 grams of gude beans produced 989 grams of gude peanut flour. Each biscuit has the same weight of 4 grams of chips. One recipe equals ± 5 ¼ servings and 1 portion equals 32 grams, namely 8 pieces of biscuits. Acceptance test of color and texture aspects there were no color differences (p = 0.660) and texture (p = 0.433) on the substitution of gude peanut flour 10%, 20% and 30%. Test of acceptance of aspects of taste and aroma there were differences in taste (p = 0.002) and aroma (p = 0.000) in substitution of gude peanut flour 10%, 20% and 30%. The conclusion obtained was that there were no color differences (p = 0.660) and texture (p = 0.433), there were differences in taste (p = 0.002) and aroma (p = 0.000) in the substitution of gude peanut flour 10%, 20% and 30%. 10% concentration has a better taste and aroma.